Visual perception and verbal response in medical communication - Ng, Desmond Boon Chiang. (2008)
The 'learning theory' has been widely known to be effective and its general psycho concept has been extrapolated theoretically in many varied situations. However, no known studies have actually been made to conclude the effectiveness of its principles between a physician-patient interaction within a clinical environment. This dissertation aims to investigate that effectiveness.